The role of ADAM8 in the mechanophenotype of MDA-MB-231 breast cancer cells in 3D extracellular matrices - Hayn, Alexander; Fischer, Tony; Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2023)
The majority of investigations of cancer cells have been performed in an oversimplified 2D in vitro environment. In the last decade there is a trend toward more sophisticated 3D in vitro cell culture model systems that can bridge the existing gap between 2D in vitro and in vivo experiments in the field of biophysical and cell biological cancer cell research. Here, we hypothesize that the bidirectional interplay between breast cancer cells and their tumor microenvironment is critical for the outcome of the disease. Thereby, the tissue remodeling processes evoked by cancer cells are important for cancer cell-driven mechanical probing of their matrix environment and on cancer cell adhesion and motility. When remodeling processes have been explored, the emphasis was placed on matrix metalloproteinases and rather not on a disintegrin and metalloproteases (ADAMs). However, the role of ADAM8 in cell mechanics regulating cellular motility in 3D collagen matrices is still unclear. Thus, in this study, we focus on the function of ADAM8 in matrix remodeling and migration of 3D extracellular matrix scaffolds. Therefore, human MDA-MB-231 breast carcinoma cells with ADAM8 knocked down, referred to as ADAM8-KD cells, as well as MDA-MB-231 scrambled control cells, referred to as ADAM8-Ctrl cells, have been used to examine their ability to interact with and migrate in dense extracellular 3D matrices. The fiber displacements, as the capacity of cells to deform the environmental 3D matrix scaffold, has been observed. ADAM8-KD cells displace collagen fibers more strongly than ADAM8-Ctrl cells. Moreover, ADAM8-KD cells migrated more numerous in 3D collagen matrices compared to ADAM8-Ctrl cells. The impairment of ADAM8 using the ADAM8 inhibitor BK-1361 led to significantly increased fiber displacements of ADAM8-Ctrl cells to the levels of ADAM8-KD cells. In contrast, the inhibitor had no effect on ADAM8-KD cells in terms of fiber displacements as well as on the quantitative characteristics of cell invasion of ADAM8-Ctrl cells, albeit the cells that were found in the matrix invaded considerably deeper. When matrix remodeling by cells is impaired through GM6001, a broad-band metalloproteinase inhibitor, the fiber displacements of both cell types increased. In fact, ADAM8 is known to degrade fibronectin in a direct and/or indirect manner. The supplementation of fibronectin before polymerization of the 3D collagen matrices caused an enhancement in fiber displacements as well as in cell invasion into fibronectin-collagen matrices of ADAM8-Ctrl cells, whereas the fiber displacements of ADAM8-KD cells did not change. However, fibrinogen and laminin supplementation induced an increase in fiber displacements of both cell types. Thus, the impact of fibronectin on selective increase in fiber displacement of ADAM8-Ctrl cells appears to be ADAM8-dependent. As a consequence, the presence of ADAM8 may provide an explanation for the longstanding controversial results of fibronectin enrichment on malignant progression of cancers such as breast cancer. Finally, ADAM8 is apparently essential for providing cell-driven fiber displacements of the extracellular matrix microenvironment, which fosters 3D motility in a fibronectin-rich environment. Contribution to the field. Currently, the role of ADAM8 has been explored in 2D or at maximum 2.5D in vitro cell culture motility assays. However, the mechanical characteristics of these two cell types have not been examined. In this study, the function of ADAM8 in breast cancer is refined by providing in vitro cell investigations in 3D collagen fiber matrices of various conditions. ADAM8 has been shown to be involved in the reduced generation of fiber displacements and in influencing breast cancer cell migration. However, especially in the presence of fibronectin in 3Dcollagen fiber matrices, the fiber displacements of ADAM8-Ctrl cells are increased.